Flashcard as an Instructional Media Towards Students’ Reading Comprehension - Yunita Rahman; Dyah Sih Pratiwi; Candraning Prihatini (ELT-Lectura, 2023)
Abstract. The purpose is to find out the using of Flashcard as an instructional media towards students’ reading comprehension. The study was done in the eleventh grade Nurul Ulum Tulung Agung Gadingrejo Pringsewu throughout the 2022–2023 academic year. The author employed action research in the classroom. Both experimental and control classes were employed by the author. The writer utilized flashcards as a learning tool in an experimental lesson, meanwhile the writer applied conventional treatment in the control group. The writer used quantitative descriptive research method. This study had a sample of 24 students as an experimental class. This study was used quantitative research. Pre-tests and post-tests were employed in the experimental class and control class to gather data. In the teaching-learning process, a test with 10 multiple-choice questions regarding the subject was used to gauge students' reading comprehension of an explanation text. This research used two cycles for the treatment in experimental class. To analyze the data was used the SPSS 16.0 App. There has been a noticeable improvement in reading comprehension skill as measured by the difference in pre- and post-test scores in the students of eleventh grade in MA Nurul Ulum Tulung Agung Gadingrejo Pringsewu. This research concluded that using Flashcard is effective as an instructional media towards students’ reading comprehension.